Non thermal technologies in the processing and conservation of vegetable foods. A review - Soleno Wilches, Ronald (Revista Colombiana de Investigaciones Agroindustriales, 2015)
During the last three decades a greater concern for consumers in the global scale regarding the quality and safety of food offered by the market has become more evident. In that sense, a marked trend towards finding healthy products and / or those that do not represent significant risks to health and moreover provide more freshness and convenience when consumption. In response, initially initiatives to eliminate the use of additives and preservatives emerged, mostly based on thermal processes (pasteurization, sterilization, freezing, etc.), that achieved to lengthen shelf life, but have direct impact on initial product characteristics (freshness, texture, nutrient content, color, etc.). In consequence focus was placed on research and development of conservation technologies they were able to keep most of the natural properties of food. The minimum processing that combines the use of plastics as a barrier, modified atmosphere (passive and active), and cold storage is the particular case of fruits and vegetables. This technology allows the production of fresh product (cut or not), but with a limited useful life period (7-15 days). Recent advances in the field are focused on the use of non-thermal technologies that are able to maintain the initial characteristics and safety of plant products for a longer period of time, although there has been progress in developing thermal technologies that reduce the negative effects on the treated products. Within the non-thermal technologies include pulsating electric fields, ultrasounds, high hydrostatic pressures, irradiation, oscillating magnetic fields, cold plasma, high-intensity white light, among others. The present review aims to study these technologies, with emphasis on the basic principles and their use in vegetal food processing. Para citar este artículo Soleno, R. (2015). Tecnologías no térmicas en el procesado y conservación de alimentos vegetales. Una revisión. Rev. Colomb. Investig. Agroindustriales, 2(1), 73-83. DOI: http://dx.doi.org/10.23850/24220582.172